2008
DOI: 10.1167/iovs.07-1347
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 7 Secretion Is Induced by Glaucoma Stimuli and Its Concentration Is Elevated in Glaucomatous Aqueous Humor

Abstract: Induction of ANGPTL7 secretion by glaucoma stimuli and increased concentration of ANGPTL7 in glaucomatous AH suggest that ANGPTL7 is overexpressed in glaucoma. Since overexpression of ANGPTL7 increases collagen expression, a potential disease mechanism, ANGPTL7 could have a pathogenic role in glaucoma, and may serve as a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 40 publications
4
47
2
Order By: Relevance
“…Both MYOC and ANGPTL-7 have previously been reported to be upregulated by GCs such as DEX. 57,58 In the present study, DEX added to HTM cells grown on hydrogels resulted in marked increases in mRNA expression of these two genes. Additionally, this DEX stimulated response of MYOC and ANGPTL-7 was even more striking in HTM cells grown on the pathomimetic substrates in comparison with the homeomimetic substrates.…”
Section: Discussionsupporting
confidence: 49%
“…Both MYOC and ANGPTL-7 have previously been reported to be upregulated by GCs such as DEX. 57,58 In the present study, DEX added to HTM cells grown on hydrogels resulted in marked increases in mRNA expression of these two genes. Additionally, this DEX stimulated response of MYOC and ANGPTL-7 was even more striking in HTM cells grown on the pathomimetic substrates in comparison with the homeomimetic substrates.…”
Section: Discussionsupporting
confidence: 49%
“…Kuchtey et al found that the concentration of ANGPTL7 was elevated in the AH of POAG eyes, supporting the notion that ANGPTL7 could be involved in POAG pathogenesis (24) . They concluded that elevated TGF-β 2 levels in glaucomatous AH could cause increased ANGPTL7 expression, which in turn could induce collagen changes, or through other mechanisms, contribute to the pathogenesis of POAG.…”
Section: Angptl7mentioning
confidence: 80%
“…34 Thus, defects in secretion of myocilin and angiopoietin-like 7 proteins have been linked to the progression of POAG, and patients with ALS exhibit abnormal secretion of growth hormone and insulin-like growth factor. [85][86][87] Another approach would be to systematically analyze the role of Optn-interacting partners in the different Optn-associated pathologies. This could be applied to decipher the role of Golgi-associated Rab8 and Htt in Glaucoma or ALS.…”
Section: Subcellular Localization Of Optnmentioning
confidence: 99%